Ethics perception: evidence from accountants and accounting students in Brazil - Lima, Jessica de Morais; Espejo, Marcia Maria dos Santos Bortolocci; Moraes, Marcelo Botelho da Costa; Lima, Emanoel Marcos (Interações, 2019)
Due to the new international ethics standards law, knowing what Brazilian accountants and accounting students perceive as ethical is extremely important. An online survey with 29 questions was conducted in MS/Brazil with different scenarios, involving different aspects that may influence someone’s decision, to assess the acceptance of unethical behaviors. The results showed difference in the ethics perception by students and accountants, but the difference was greater based on gender.